IMPACT ANALYSIS FOR THE REGULATION OF COMPENSATION MECHANISMS FOR ECOSYSTEM SERVICES - Blas Ochochoque, Stefani (2019)
The objective of this document is to perform an impact analysis for the regulation of Compensation Mechanisms for Ecosystem Services in the Peruvian Amazon based on evidence fromLatinAmerica.The investigation is divided into three chapters. The first chapter aims to expose the motivation of this work, identifying the problem and the corresponding objectives. The second chapter contains the general context of the departments of the jungle and the experiences of the execution of the Mechanisms of Compensation for Ecosystem Services in Costa Rica and Brazil. In the next chapter, a balance is made in the form of a qualitative cost - benefit analysis and a multicriteria analysis.